Faith and Forgiveness: Lessons in Statecraft for Queen Mary Tudor - Attreed, Lorraine Christine (The sixteenth century journal, 2005)
The last work of English humanist Henry Parker, Lord Morley, "An Account of Miracles Performed by the Holy Eucharist," contained valuable advice for the realm's first ruling queen, Mary Tudor. Cognizant of the special challenges facing a female ruler, Morley delineated guidelines enabling the new queen to combine an active public life with traditional pious devotions to which Mary was committed. He drew examples from recent and distant English history, citing the regimens of Mary's own great-grandmother Lady Margaret Beaufort and of twelfth-century queen Edith Maude. In direct response to political and economic dilemmas, Morley's work assured the queen of the rectitude of her religious stance. Morley's historical examples attempted a complex balance, reinforcing the power of the monarchy and moderating its harshest instincts. Morley also cited examples from his own life, not only to describe a proper role model for the queen but to explain and find forgiveness for his survival through more than seven decades of Tudor rule.